2023
DOI: 10.1186/s12884-023-05516-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the clinical outcomes of microbial contamination caused by environmental contamination of the embryology laboratory during IVF-ET treatment cycles

Abstract: Background Bacterial contamination may cause loss of or damage to cultured oocytes or embryos, resulting in the lack of transplantable embryos during IVF embryo culture. However, there are few reports about IVF embryo contamination caused by embryology laboratories. In this work, we evaluated clinical pregnancy outcomes and the risk of maternal and infant complications after embryo contamination caused by environmental pollution during IVF. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Zheng et al 18 , reported for the first time that embryo contamination caused by Staphylococcus pasteuri colonization does not seem to have an effect on laboratory outcome and pregnancy outcome of embryos. In Maduka and colleagues’ study, 80 patients were selected and both catheter tip and cervical swabs were prepared and cultured.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al 18 , reported for the first time that embryo contamination caused by Staphylococcus pasteuri colonization does not seem to have an effect on laboratory outcome and pregnancy outcome of embryos. In Maduka and colleagues’ study, 80 patients were selected and both catheter tip and cervical swabs were prepared and cultured.…”
Section: Discussionmentioning
confidence: 99%